Prognosis of lymphadenectomy in malignant ovarian germ cell tumor - Lv, Bin; Liu, Xinghui; Zheng, Ai; Han, Ling (Frontiers in Oncology, 2023)
Background and Objectives: The routine application of lymphadenectomy remains a controversial part of surgical staging in malignant ovarian germ-cell tumor (MOGCT). Thus, studies are needed to explore the prognostic significance of lymphadenectomy in MOGCT. The goal of this retrospective study was to report the clinical outcomes of lymph node dissection (LND) and non-LND in MOGCT surgeries. Measurements and main results: A total of 340 cases of MOGCTs were included: 143 patients (42.1%) had LND and 197 (57.9%) had no LND. The OS rates at 5 years in the LND and non-LND group were 99.3% vs. 100%, respectively. The DFS rates at 5 years in the LND and non-LND group were 88.8% vs. 88.3%. Forty-three patients (12.6%) were successfully pregnant during the postoperative follow-up. There were 44 recurrences (12.9%) and six deaths (1.8%). Stage was an independent prognostic factor for DFS in the multivariate analysis. Pathology was reported as an independent prognostic factor associated with OS in the multivariate analysis. Conclusion: Lymphadenectomy had no significant influence on the OS (P=0.621) or disease-free survival rate (P=0.332) of patients with MOGCT.